ผลของดนตรีต่อความวิตกกังวลในสตรีตั้งครรภ์ที่ได้รับการเจาะตรวจน้ำคร่ำ Effect of Music on Anxiety Among Pregnant Women Undergoing Amniocentesis - นิคม อรนิด; เฉลิมสุข นงลักษณ์; ศุภวิทิตพัฒนา บังอร (วารสารการพยาบาลและการดูแลสุขภาพ, 2019)
Amniocentesis is a prenatal diagnostic procedure for detecting fetal chromosomal abnormality, which induces anxiety in pregnant women waiting to undergo amniocentesis. The purpose of this quasi-experimental study was to examine the effect of music on anxiety among pregnant women waiting to undergo an amniocentesis. 50 pregnant women had gestational age between 15 and 20 weeks who were waiting to first undergo an amniocentesis at antenatal care unit of Udon Thani Hospital between June and July 2018. The samples were purposively selected and assigned into an experimental group and a control group with twenty-five in each group which was matched according to anxiety scores and age. The experimental group listened to music with receiving routine nursing care and the control group only received routine nursing care. The results were measured with the following research instruments: instrumental music (i.e., no lyrics, slow rhythm approximately 60 to 80 times per minute, and duration of music 30 minutes), a demographic data form and 3) the six-item short form of the State Anxiety Inventory developed of the Spielberger Anxiety Inventory. Data were analyzed using descriptive statistics, independent t- test, and paired t-test. The results revealed that The pregnant women waiting to undergo an amniocentesis who listened to music had statistically significant less anxiety compared with the anxiety they felt prior to listening to music (p <.001). When comparing with group the results revealed that: The experimental group had statistically significant less anxiety than the control group (p <.001). The findings of this study suggest that health care providers can use music to reduce anxiety among pregnant women waiting to undergo an amniocentesis.